Optimalisasi Program Tahfidz Qur’an: Pendekatan Konsistensi Dan Evaluasi Intensif Untuk Mencapai Target Hafalan Di Pesantren - Ulfiana, Nila Hanif; Kholifiana, Nanda Intan; Al Rosid, Moh. Harun; Kholiq, Ilham Nur (Civiliza Publishing, 2024)
Education at Islamic boarding schools has an important role in shaping the character and knowledge of the younger generation, especially in memorizing the Koran. However, students often face challenges in dividing their time between formal education and activities at Islamic boarding schools, which results in neglected memorization. To overcome this problem, this service aims to optimize the tahfidz program by implementing consistency in murojaah and intensive evaluation. This program was implemented at the Al Aziziyah Dormitory, using a Participation Action Research (PAR) approach. The PAR process involves five steps: problem identification through discussion, planning murojaah consistency strategies and evaluation, implementing actions, observing memorization development, and evaluating implementation results. Murojaah consistency, which is routine rote repetition, has been proven to be effective in strengthening memory and maintaining long-term memorization. Regular evaluation through daily and weekly exams helps monitor student progress and allows for quick identification of deficiencies. Teacher training is also important to ensure they have the ability to support students with effective methods. Based on interviews with program coordinators, students who are consistent in murojaah show better results than those who only focus on adding new memorization. Through a combination of repetition strategies, systematic evaluation and teacher training, the tahfidz program is expected to improve the quality of students' memorization.